Implikasi Faktor Makroekonomi terhadap Kinerja Keuangan Bank BUMN di Indonesia dalam Satu Dekade - Susilo, Bambang (Transpublika Publisher, 2025)
The banking sector has a strategic role in Indonesia's economic growth, with state-owned banks as the main pillars of the national financial system. This study is intended to evaluate the impact of macroeconomic factors on the financial performance of state-owned banks during the period 2014-2023 using Return on Assets (ROA) as a performance indicator. This quantitative research with panel data regression method uses independent variables of interest rate, inflation, and exchange rate. Secondary data was obtained from the financial statements of four state-owned banks (BRI, BNI, Mandiri, and BTN) analyzed using STATA 17. The study states that interest rates have a significant positive impact on ROA, while inflation only has an insignificant positive impact and exchange rates have an insignificant negative impact on ROA. The research findings indicate that state-owned banks have good adaptability in dealing with fluctuations in macroeconomic conditions. This study contributes to the understanding of the dynamics of national banking financial performance and suggests the importance of paying attention to interest rates in bank management strategies.